2006
DOI: 10.1093/toxsci/kfl185
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of the Estrogenic, Androgenic, and Progestagenic Potential of Two Cyclic Siloxanes

Abstract: The purpose of these experiments was to determine the potential estrogenic, androgenic, and progestagenic activity of two cyclic siloxanes, octamethylcyclotetrasiloxane (D4) and decamethylcyclopentasiloxane (D5). Receptor-binding experiments and a luciferase reporter gene assay were used to determine if the materials were able to bind and activate either the estrogen receptors (ERs) or progesterone receptors (PRs)-alpha or beta. The rat uterotrophic assay (RUA) for estrogenic activity and the Hershberger assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(45 citation statements)
references
References 24 publications
4
41
0
Order By: Relevance
“…Significant gaseous exchange via the lungs is predicted in air breathing organisms [42], suggesting that c-VMS may not bioaccumulate in birds, cetaceans and pinnipeds. Moreover, in vitro exposure to D4 via injection in mice caused fatal liver and lung damage [43], oral exposure to D4 caused oestrogenic effects [44][45][46] and inhalation of D5 affected the nervous system [47]. In the case of human beings, although in short-term and controlled studies no immunologic or pro-inflammatory effects of D4 were observed, the European Union suggested some damaging effects on hormone function that may result in infertility [48].…”
Section: Environmental and Health Risk Concerns Of Siloxanesmentioning
confidence: 99%
“…Significant gaseous exchange via the lungs is predicted in air breathing organisms [42], suggesting that c-VMS may not bioaccumulate in birds, cetaceans and pinnipeds. Moreover, in vitro exposure to D4 via injection in mice caused fatal liver and lung damage [43], oral exposure to D4 caused oestrogenic effects [44][45][46] and inhalation of D5 affected the nervous system [47]. In the case of human beings, although in short-term and controlled studies no immunologic or pro-inflammatory effects of D4 were observed, the European Union suggested some damaging effects on hormone function that may result in infertility [48].…”
Section: Environmental and Health Risk Concerns Of Siloxanesmentioning
confidence: 99%
“…One study looked at use of personal care products in a cohort of 94 postmenopausal women in Norway and serum levels of estrogenic (20) and anti-androgenic (21) cyclic volatile methylsiloxanes (cVMS) (22). Sources of exposure to cVMS are generally through cVMS present in personal care products, inhalation due to the volatility of the compounds, or cVMS contained in breast implants (22).…”
Section: Chemicals In Cosmetics and Their Detectionmentioning
confidence: 99%
“…In a recent peer-reviewed paper, Quinn et al (2007) used receptor-binding experiments and a luciferase reporter gene assay to determine if D5 was able to bind and activate either the estrogen receptors (ERs) or the progesterone receptors (PRs). They used the rat uterotrophic assay (RUA) for estrogenic activity and the Hershberger assay for androgenic activity as in vivo assays.…”
Section: Hormonal Effectsmentioning
confidence: 99%